Reorganizing outpatient spine services increased efficiency and patient satisfaction - Arkan Sam Sayed-Noor; Thomas Torstensson; Björn Knutsson (Brain and Spine)
Introduction: The workload in orthopedic outpatient departments is increasing while the available medical resources are often limited. Research questions: Can reorganizing the outpatient work routines for referred patients with spinal disorders improve cost-effectiveness and patient's experience of care (PEC) without negatively affecting the waiting time required for the healthcare guarantee? Material and methods: We compared our standard routine (control group) to a new routine (study group) for evaluating referrals of patients with spinal complaints. In the control group, the referral was first evaluated by a spinal surgeon, and when deemed indicated, a visit to a spinal surgeon was booked. In the study group, a spinal surgeon first evaluated all referral notes and either assigned a spinal surgeon or a physiotherapist to meet the patient, depending on certain criteria. If considered eligible for surgical intervention, the patient is appointed for a follow-up visit to the spinal surgeon. For both groups, calculations were made for the number of waiting days and visits, as well as the cost. Also, we compared the PEC between the two groups through telephone interviews. Results: The number of waiting days and visits, as well as the cost, were significantly reduced (p < 0.01) in the study group. Also, the study group showed slightly higher mean values for the PEC components, with significant differences related to the waiting time, treatment with respect, and taking account of patient knowledge. Discussion and conclusions: Reorganizing outpatient work routines could eliminate the need for locum doctors while maintaining patient satisfaction and reducing costs.